CLOSURE OF ELECTIVE ABDOMINAL INCISIONS WITH MONOFILAMENT, NON-ABSORBABLE SUTURE MATERIAL VERSUS POLYFILAMENT ABSORBABLE SUTURE MATERIAL - Talpur, Altaf Ahmed; Awan, Mohammad Sharif; Surhio, Abdul Rasheed (Journal of Ayub Medical College Abbottabad, 2011)
Background: Closure of abdominal incisions with different suture materials has been a matter of great controversy. Polypropylene and Polylactide with Polyglycolide are among the commonest suture materials used for closure of abdominal incisions. Objectives of this study were to assess optimal suture material used for closure of elective abdominal incisions and to see complications associated with these suture materials. Methods: This prospective, comparative, randomised study was conducted at public and private sector hospitals of Nawabshah and Hyderabad from 1st Jan 2005 to 31st October 2009. All patients who underwent abdominal surgery under the investigators' supervision were included in the study. Patients were divided into 2 groups on even or odd numbers. In group-A patients' incision was closed with monofilament, non-absorbable Polypropylene (Prolene) No. 1 suture material and in groupB incision was closed with Polyfilament, absorbable, co-polymer of Polylactide with Polyglycolide (Vicryle) No. 1. Results: A total 274 patients were finally analysed for closure of elective abdominal incisions, with 138 (50.4%) patients in Group-A and 136 (49.6%) patients in Group-B. Vicryle was found superior in knot security and suture handling. Superficial wound infection was found in 5.79% patients of Group-A and 6.61% of Group-B. Discharging sinus was found in 3.62% of Group-A vs 0.73% of Group-B. Burst abdomen was seen in 2.17% patients in Group-A and 1.47% in Group-B. Incisional hernia was present in 4.34% of Group-A and 0.73% patients of Group-B. No patient in Group-B developed persistent pain at incisional site while it was found in 8.69% patients of Group-A. Conclusion: Polylactide is an optimal suture material in closure of elective abdominal incisions. Keywords: elective, incisions, monofilament, polyfilament, suture, postoperative, complications